2011
DOI: 10.1108/01425451111096659
|View full text |Cite
|
Sign up to set email alerts
|

Flexible working and happiness in the NHS

Abstract: Purpose-This paper aims to explore the influence of flexible working on employee happiness and attitude, and the role of this within a high performance work system (HPWS). Design/methodology/approach-A case study of flexible working within an NHS Acute Trust is presented. A qualitative study is undertaken based on 43 employee interviews across a range of directorates within the Trust. Findings-Employees perceive that flexible working makes them "happy" and that there are attitudinal/behavioural links between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 44 publications
3
64
0
4
Order By: Relevance
“…It should be noted that work flexibility offers convenience in planning, not reducing the working time. Thus, flexibility in work might be summarized as the ability of employee to control his/her working time duration as well as location of work (remotely from office), this ability in scheduling Impact of Flexible Working Hours on Work-Life Balance 21 work suppose to be offered by employer [8].…”
Section: Flexible Working Hoursmentioning
confidence: 99%
“…It should be noted that work flexibility offers convenience in planning, not reducing the working time. Thus, flexibility in work might be summarized as the ability of employee to control his/her working time duration as well as location of work (remotely from office), this ability in scheduling Impact of Flexible Working Hours on Work-Life Balance 21 work suppose to be offered by employer [8].…”
Section: Flexible Working Hoursmentioning
confidence: 99%
“…A study carried oft by Zeytinoğlu et al on the subject (2011) found that compared to those in full-time employment, nurses in part-time employment do not intend to leave the profession. Atkinson and Hall's (2011) research which studied on nurses shows that flexible working practices have a range of positive outcomes including enhanced patient care reduced nurse turnover, reduced use of temporary staff hours and lower sickness absence (Atkinson and Hall, 2011). As seen, researches show that flexible working practice often reduces the turnover and absenteeism rate.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the research conducted with 100 people, Jain and Swami (2014) defend that flexible working is a good policy in order to keep qualified employees in the organization for growing economies and competitive markets. As well as the most of researches about flexible working focus positive outcomes in a variety of measures of work performance, there are also some limited evidence to support positive employee outcomes like improved satisfaction among staff and improved health and wellbeing (Atkinson and Hall, 2011).…”
Section: Flexible Working Subjective Well-being and Intention To Leavementioning
confidence: 99%
“…There is, however, criticism in Western literature of commitment's dominance and a recognition that other attitudes require investigation (Atkinson & Hall, 2011;Macky & Boxall, 2007). Here we address two attitudes that are widely recognised as important, job satisfaction (Chang, Liangding, Takeuchi, & Cai, 2014;Kim et al, 2010) and trust .…”
Section: Employee Attitudesmentioning
confidence: 94%